Evaluating the impact of coenzyme Q10 and high-intensity interval training on lactate threshold and Plasma blood gases in rats: a randomized controlled trial - Yasul, Yavuz; Yilmaz, Busra; Senel, Omer; Kurt, Dursun; Akbulut, Taner; Calikusu, Aysen; Yilmaz, Canan (Springer, 2025)
Purpose Coenzyme Q(10) (Q(10)) is a mitochondrial coenzyme that facilitates ATP production via oxidative phosphorylation. This study hypothesized that Q(10) enhances mitochondrial efficiency and lactate threshold, while high-intensity interval training (HIIT) promotes metabolic adaptations, improving glucose utilization and buffering capacity for faster recovery after high-intensity exercise. Methods A randomized controlled trial was conducted using 24 male Sprague-Dawley rats (250.4 +/- 6.1 g, 8 weeks old). The rats were allocated into four groups: control (C), coenzyme Q(10) (CoQ(10)), HIIT, and HIIT + Q(10). The Q(10) administration involved a dosage of 10 mg/kg/day, given 30 min prior to the HIIT protocol. Lactate threshold, blood gas parameters, oximetry values, metabolite levels, and electrolyte status were analyzed utilizing the Radiometer 900 device. The blood samples were collected at the fifth and tenth minutes following the HIIT training trials. Results The HIIT + Q(10) group exhibited a significant reduction in lactate threshold (p < 0.01), maintaining values below average. Significant improvements in blood gas parameters, including pH, pO2, and pCO2, were observed in this group. Enhanced oxygen transport capacity was indicated by improved oximetry parameters (Hb, HCT, sO(2)) and reduced COHb levels. Additionally, positive changes in HCO3- and base values indicated reduced metabolic stress. Q(10) supplementation also stabilized electrolytes, particularly K+ and Na+. Conclusion The Q(10) supplementation supported metabolic balance, improved oxygen transport, and stabilized acid-base levels during HIIT. It reduced lactate accumulation, enhanced glucose availability, and alleviated metabolic stress, thereby improving recovery efficiency and physiological adaptation.
Keywords: Blood gases; Coenzyme Q(10); HIIT; Lactate threshold; Oxygenation; Recovery